Students’ Perceptions on Using Whatsapp and Youtube Applications in English Online Learning - Zellya Ayu Andini; M. Affandi Arianto (Universitas Negeri Padang, 2023)
Since the pandemic of COVID-19, Online learning has recently grown in popularity due to reduce the interactions in learning and ease of access to content of learning at any time from any place which is no longer limited to the physical classroom. Then, social media is a technology tool commonly utilized by teachers in online learning that has evolved into an alternative for teachers and students to promote online teaching and learning and some English teachers combined WhatsApp and YouTube in online learning. This study was to close the gap by investigating students' perceptions of using WhatsApp and YouTube in English online learning at SMA N 5 Sijunjung by using TAM (perceived ease of use, perceived usefulness, attitude toward using, and behavioral intention). To address the issue, the present study sheds some light on 34 students’ perceptions toward WhastApp and YouTube in English online learning at SMA Negeri 5 Sijunjung. Drawing on the data from a web-based survey and interview. The results show that the mean of perceived ease of use is 2.75, perceived usefulness is 2.78, attitude toward using is 2.77, behavioral intention is 2.73 and actual usage is 2.67. Students positively perceived the ease of use and usefulness on using WhatsApp and YouTube in English online learning. Students also like and intend to use WhatsApp and YouTube English online learning. And it was also revealed that students also found few difficulties to understand video explanation because they still need teacher explanation about the material.